Influence of vegetarian diet on human body - Piotr Wójcik; Monika Rogowska; Małgorzata Chyćko; Jan Tomczyk; Anna Sobstyl; Danuta Krasowska; Marta Kozłowska (Kazimierz Wielki University, 2020)
All over the world there are more vegetarians than in previous years due to many reasons. One of them is positive influence on health what is shown in the latest research. The aim of the article is to review the influence of vegetarian diet on frequent diseases such as: hypertension, obesity,osteoporosis. An analysis of scientific papers from Pubmed and Google Scholar was performed, which most accurately described the issue of impact vegetarian diet on human health. The following keywords have been used in the search:Vegetarian, hypertension, obesity, osteoporosis:vegetarian, hypertension, obesity, osteoporosis. The researchers shown than vegetarians have lover systolic blood pressure  and diastolic blood pressure by 10 and 5 mmHg, they also lower overall mortality by 10-15%, risk of heart failure and by ~40%,  stroke by~35% and coronary events by 20%.  Vegetarians also have statistically  lower body mass index. What's more in this diet is more energy efficient thanks too low food energy density and helps keeping leptin on adequate level.  Research has shown than vegetarians have lower mineral bone density than non-vegetarian, although some studies has shown that  risk of fractures in vegetarians and non-vegetarians was not affected by diet alternation.  Based on the results of the studies above vegetarian diet contributes to lower blood pressure and preventing from cardiovascular diseases. It helps to avoid obesity and  to get rid of weights also doesn't have negative impact on osteoporosis.